The family plot ebook A novel. - Collins, Megan (2021)
A family obsessed with true crime gathers to bury their patriarch—only to find another body already in his grave in this "moody and atmospheric" ( USA TODAY ) thriller. Raised in a secluded island mansion deep in the woods and kept isolated by her true crime-obsessed parents, twenty-six-year-old Dahlia Lighthouse is still haunted by her twin brother Andy's disappearance a decade ago. After several years away and following her father's death, Dahlia returns home, where the family makes a gruesome discovery: buried in their father's plot is another body—Andy's, his skull split open with an ax. Dahlia is quick to blame Andy's murder on the serial killer who terrorized the island for decades, while the rest of her family reacts to the revelation in unsettling ways. Her brother, Charlie, pours his energy into creating a family memorial museum, highlighting their research into the lives of famous murder victims; her sister, Tate, forges ahead with her popular dioramas portraying crime scenes; and their mother affects a cheerfully domestic facade, becoming unrecognizable as the woman who performed murder reenactments for her children. As Dahlia grapples with her own grief and horror, she realizes that her eccentric family, and the mansion itself, may hold the answers to what happened to her twin in this "gorgeously wrought and deliciously creepy...twisted delight" (Kathleen Barber, author of Follow Me ).